2022
DOI: 10.1001/jamaoncol.2021.6214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadotropin-Releasing Hormone Analogs on Ovarian Function Against Chemotherapy-Induced Gonadotoxic Effects in Premenopausal Women With Breast Cancer in China

Abstract: IMPORTANCEStudies of the use of gonadotropin-releasing hormone analogs (GnRHa) to protect ovarian function have shown mixed results.OBJECTIVE To determine whether administering GnRHa during chemotherapy in premenopausal women with breast cancer can reduce ovarian impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…This study showed that GnRHa treatment was an important factor affecting the incidence of POI: The risk of POI in patients with combined GnRHa was only 0.09 times that in those without combined GnRHa. Meanwhile, the probability of ovarian function recovery in patients with short-term ovarian function impairment after chemotherapy was 18.49 times higher in patients with GnRHa combination than in patients without GnRHa combination, which was consistent with the results of our own laboratory and clinical studies and with the results of most studies [ 3 , 9 , 10 , [20] , [21] , [22] , 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study showed that GnRHa treatment was an important factor affecting the incidence of POI: The risk of POI in patients with combined GnRHa was only 0.09 times that in those without combined GnRHa. Meanwhile, the probability of ovarian function recovery in patients with short-term ovarian function impairment after chemotherapy was 18.49 times higher in patients with GnRHa combination than in patients without GnRHa combination, which was consistent with the results of our own laboratory and clinical studies and with the results of most studies [ 3 , 9 , 10 , [20] , [21] , [22] , 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…The trial was conducted at the Shanghai Jiao Tong University Affiliated Shanghai Sixth People's Hospital in Shanghai and Zhejiang Cancer Hospital in Hangzhou, China. The trial protocol and all amendments that approved by an independent ethics committee or the institutional review board at each site were published [ 22 ]. Written informed consent was provided by all the patients.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the protective effect of GnRHa on ovary during chemotherapy has attracted attention. Several meta-analysises and prospective randomized studies (11,12) have shown that GnRHa signi cantly reduces the risk of POF in women undergoing gonadal toxic chemotherapy. Although these results seem promising, a paucity of data exists on similar use of GnRHa in the HSCT population, especially in China.…”
Section: Introductionmentioning
confidence: 99%